ENHANCING ENGLISH TEACHERS' PROFESSIONAL DEVELOPMENT: PORTRAYING A MENTORING PROGRAM - Rohmah, Zuliati (TEFLIN Journal, 2018)
Quality English teachers are required to have a good mastery of English language skills and language teaching methodology. New teachers or lecturers, in particular, need assistance in improving these two aspects. One of the ways is through Continuing Professional Development (CPD). Traditionally, professional development (PD) is done by attending professional forums and pursuing further education. However, this traditional practice has some weaknesses, one of which is giving little opportunity for teachers to take control over their own learning (Kennedy, 2005; Rose & Reynolds, 2007). While mentoring practices as a form of CPD are common in more developed countries, they are not widely practiced in Indonesia. To respond to the scarcity of research in this area, the current study is conducted by using observations and questionnaire as the instruments to portray the implementation of a mentoring program in an English training institution in East Java, Indonesia. Specifically, the article reports the practice of the mentoring program and the mentees' perceptions of the mentoring sessions with the mentor. The findings show that the teachers respond positively to the mentoring program, and they also feel that their self-confidence is improved after joining the program. The mentoring program conducted in the institution helps the teachers to enhance their professionalism as English teachers.